1999
DOI: 10.1016/s0020-7292(99)00007-7
|View full text |Cite
|
Sign up to set email alerts
|

Timing of suicide attempts by self‐poisoning during pregnancy and pregnancy outcomes

Abstract: Most suicide attempts by self-poisoning occurred after the early recognition of unwanted pregnancies and most resulted in a very early fetal loss. Pregnancies with advanced gestation months had a significantly lower proportion of attempting suicide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 17 publications
0
21
0
Order By: Relevance
“…The majority of studies that have assessed the impact of suicidal ideation during pregnancy on fetal development have done so in the context of self-poisoning. A series of 15 articles were published from the Budapest Monitoring System of Self-Poisoning Pregnant Women that evaluated the potential effects of large doses of drugs on fetal development among pregnant women who attempted suicide (Czeizel et al, 1997, Czeizel et al, 1999, Timmermann et al, 2009, Gidai et al, 2008c, Gidai et al, 2008a, Gidai et al, 2008d, Gidai et al, 2008b, Gidai et al, 2010, Petik et al, 2008a, Petik et al, 2008b, Petik et al, 2012, Timmermann et al, 2008b, Timmermann et al, 2008a, Timmermann et al, 2008c). With regards to congenital anomalies, the primary outcomes of these studies, no statistically significant associations were reported with self-poisoning (Czeizel et al, 1997, Czeizel et al, 1999, Timmermann et al, 2009, Gidai et al, 2008c, Gidai et al, 2008a, Gidai et al, 2008d, Gidai et al, 2008b, Gidai et al, 2010, Petik et al, 2008a, Petik et al, 2008b, Petik et al, 2012, Timmermann et al, 2008b, Timmermann et al, 2008a, Timmermann et al, 2008c).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of studies that have assessed the impact of suicidal ideation during pregnancy on fetal development have done so in the context of self-poisoning. A series of 15 articles were published from the Budapest Monitoring System of Self-Poisoning Pregnant Women that evaluated the potential effects of large doses of drugs on fetal development among pregnant women who attempted suicide (Czeizel et al, 1997, Czeizel et al, 1999, Timmermann et al, 2009, Gidai et al, 2008c, Gidai et al, 2008a, Gidai et al, 2008d, Gidai et al, 2008b, Gidai et al, 2010, Petik et al, 2008a, Petik et al, 2008b, Petik et al, 2012, Timmermann et al, 2008b, Timmermann et al, 2008a, Timmermann et al, 2008c). With regards to congenital anomalies, the primary outcomes of these studies, no statistically significant associations were reported with self-poisoning (Czeizel et al, 1997, Czeizel et al, 1999, Timmermann et al, 2009, Gidai et al, 2008c, Gidai et al, 2008a, Gidai et al, 2008d, Gidai et al, 2008b, Gidai et al, 2010, Petik et al, 2008a, Petik et al, 2008b, Petik et al, 2012, Timmermann et al, 2008b, Timmermann et al, 2008a, Timmermann et al, 2008c).…”
Section: Resultsmentioning
confidence: 99%
“…The majority of drugs used for self-poisoning in these studies were also not associated with mental retardation, low birth weight, or preterm birth. However, investigators found that large doses of Tardyl (combination of amobarbital, glutethimide, and promethazine) were associated with an increased prevalence of mental retardation among exposed infants compared to their unexposed siblings (29.6% vs. 0%, p<0.0001) (Petik et al, 2012) and that self-poisoning during pregnancy was associated with increased odds of very early fetal loss (OR=6.09, 95% CI: 3.82–9.71) and decreased odds of live birth (OR=0.08, 95% CI: 0.23–0.72) (Czeizel et al, 1999). …”
Section: Resultsmentioning
confidence: 99%
“…Women who die from homicide during pregnancy are often not included in maternal mortality statistics. Based on reviews of 651 autopsy charts of women aged 15 to 50 who died during an 8-year period of time in Washington, DC, Krulewitch 34 Sao Paulo, Brazil 1988 -1997 Accidents and homicides combined 3 Czeizel AE, et al 35 Budapest, Hungary 1985-1993 Suicide attempts and low numbers 2 suicides Rizzi RG, et al 36 Argentina 1992-1996 Low numbers 1 homicide, 2 suicides Harper MA, et al 37 North Carolina, USA 1992-1994 Duplicate dataset 22 homicides, 5 suicides Gissler M, et al 38 Finland 1987-1994 Duplicate dataset Frautschi S, et al 39 Worldwide 1960 -1994 Review article 0 Harris C, et al 40 Gales, England 1990…”
Section: Discussionmentioning
confidence: 99%
“…Twenty-one articles, which contained numbers of suicides during and after pregnancy, are included in Table 2 (6,7,9,10,2,16,(18)(19)(20)(21)(22)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33). The 16 articles that met exclusion criteria are compiled in Table 3 (23,(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46). Studies were excluded if they contained duplicate datasets, case reports of less than 3 events, or suicide attempts only.…”
Section: Sourcesmentioning
confidence: 99%
“…The majority of such episodes are impulsive and frequently precipitated by violent interpersonal disputes [12]. The peak time reported for self-harm attempts in pregnancy is the first trimester, after which, it declines with advanced gestational age [8,9,11,[13][14][15].…”
Section: Discussionmentioning
confidence: 99%